PERAWATAN PAYUDARA DALAM KEHAMILAN DAN PEMBERIAN ASI EKSLUSIF (Jurnal Kesehatan Siliwangi, 2021)
Breast milk is a liquid that comes out of a mother's breast which contains various nutrients according to the baby need. Exclusive breastfeeding is feeding the baby in the form of breast milk without other additional food until the baby is 6 months old. Exclusive breastfeeding is important because it makes the baby experience normal growth and development, prevents obesity, controls optimally weight, also forms the closeness of mother and child. Knowledge, information, and a small amount of breast milk production are the triggers for the low coverage of exclusive breastfeeding in Subang Regency in 2016 which is 39 The efforts to succeed in exclusive breastfeeding can be done since pregnancy, one of which is by carrying out routine breast care during pregnancy. The aims of this report is to be able to carry out comprehensive midwifery care with the application of breast care during pregnancy, so that it can support the success of exclusive breastfeeding. The method used is a case study, by providing comprehensive midwifery care to a client since the third trimester of pregnancy, childbirth, postpartum and care for newborns at the Independent Midwife Practice on April 19 to June 11, 2021. Breast care provided during pregnancy includes carry out Educational Information Communication (IEC) on breast care in the third trimester of pregnancy, the importance of breast hygiene especially the nipples, the benefits of exclusive breastfeeding, regulating nutrition and rest patterns, breast care during postpartum, and expressing breast milk. The results of the care can be seen where the client's confidence in exclusive breastfeeding increases, the milk production runs smoothly without obstacles, and the baby is healthy with normal weight.This shows that breast care during pregnancy has an effect on milk production so that it is proven to support exclusive breastfeeding.